2016
DOI: 10.1039/c6ra12144f
|View full text |Cite
|
Sign up to set email alerts
|

Novel magnetic core–shell Ce–Ti@Fe3O4 nanoparticles as an adsorbent for water contaminants removal

Abstract: Magnetic core-shell Ce-Ti@Fe 3 O 4 nanoparticles were synthesized by coating cerium titanate on magnetite under mild experimental conditions. Combining magnetism, crystallinity, stability and adsorption capacity, it can be a promising nanomaterial as an adsorbent for anionic water contaminants, exhibiting high removal capacity, from 85% to 100%, for nitrates, phosphates and fluoride.Contamination of water is a widespread problem throughout the world as a result of pollution and a wide range of pollutants can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 46 publications
(18 reference statements)
0
11
0
Order By: Relevance
“…Several articles on water purification processes using NPs have been published focusing on the removal of metals (Contreras et al, 2015;Recillas et al, 2010;Sánchez et al, 2011;Xu and Zhao, 2007) or nutrients (Abo Markeb et al, 2016a;Abo Markeb et al, 2016b;Choe et al, 2000;Sá et al, 2009). This shows the potential of nanotechnology to remove contaminants.…”
Section: Capture Of Ghgs Via Sorptionmentioning
confidence: 99%
“…Several articles on water purification processes using NPs have been published focusing on the removal of metals (Contreras et al, 2015;Recillas et al, 2010;Sánchez et al, 2011;Xu and Zhao, 2007) or nutrients (Abo Markeb et al, 2016a;Abo Markeb et al, 2016b;Choe et al, 2000;Sá et al, 2009). This shows the potential of nanotechnology to remove contaminants.…”
Section: Capture Of Ghgs Via Sorptionmentioning
confidence: 99%
“…8 and 9 in Section 3.2, respectively). According to the literature, phosphate adsorption by some non-LDH adsorbents [66][67][68][69][70] and some LDH adsorbents [23][24][25][26]31,33 is greatly affected by F À or Cl À due to their adsorption. For LDHs, considering the bonding strength between the layers and interlayer anions in aqueous solution, 17 the strength of phosphates is generally higher than that of F À and Cl À .…”
Section: àmentioning
confidence: 99%
“…Chen et al [20] used a MIL-100 (Fe) On the other hand, magnetite has proven to be an excellent candidate for removing pollutants in an aqueous medium [13]. Its ability to incorporate quite well with other materials [14][15][16] increases adsorption capacity and recovery in aqueous medium and thermal stability [17]. Although MOFs included with magnetite have already been studied, few have been applied to remove contaminants in aqueous media [14,18].…”
Section: Introductionmentioning
confidence: 99%
“…Its ability to incorporate quite well with other materials [ 14 , 15 , 16 ] increases adsorption capacity and recovery in aqueous medium and thermal stability [ 17 ]. Although MOFs included with magnetite have already been studied, few have been applied to remove contaminants in aqueous media [ 14 , 18 ]. Giesy et al [ 19 ] reported one of the first works to incorporate magnetite in MOFs using HKUST-1 included with magnetic material to remove colorants from water, showing a clear increase in the removal capacity of methylene blue.…”
Section: Introductionmentioning
confidence: 99%